Penerapan Aplikasi Berbasis Android Untuk Ternak Ayam Petelur Sebagai Wadah Untuk Menghubungkan Pemilik Modal Dengan Calon Peternak - Sudianto, Aris; Sadali, Muhamad (Infotek : Jurnal Informatika dan Teknologi, 2021)
Laying hens are one of the producers of animal protein through the production of eggs, eggs that contain many nutrients needed by the body. The need for chicken eggs in NTB in 2019 reaches 1.3 million eggs, but regional layer hen breeders are only able to produce as many as 6000 eggs so that to meet the need for eggs, the government needs to bring eggs from other regions. The government also encourages people to raise laying hens through the poultry village program, which is one of the industrialization programs in the livestock sector to make NTB egg independent. However, to start raising livestock there are several problems that become sellers, namely the problem of capital and land. People who have capital do not have the choice of where to invest their money in the end only save their money in a bank whereas on the other hand farmers who own land need capital to start a livestock business. Therefore, the authors provide a solution by creating a well-known application as a place to connect investors with prospective breeders through an Android-based application so that investors can easily find potential breeders and breeders find it easier to get capital to start raising laying hens